Serological Evidence of Rickettsia Exposure among Patients with Unknown Fever Origin in Angola, 2016-2017 - Barradas, P. F.; Neto, Z.; Mateus, T. L.; Teodoro, A. C.; Duarte, L.; Gonçalves, H.; Ferreira, P.; Gärtner, F.; Sousa, R.; Amorim, I. (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Spotted fever group Rickettsia (SFGR) is one among the aetiologies that cause fever of unknown origin in Angola. Despite their occurrence, there is little information about its magnitude in this country either because it is misdiagnosed or due to the lack of diagnostic resources. For this purpose, eighty-seven selected malaria- and yellow fever-negative serum specimens collected between February 2016 and March 2017 as part of the National Laboratory of Febrile Syndromes, from patients with fever (≥37.5°C) for at least 4 days and of unknown origin, were screened for Rickettsia antibodies through an immunofluorescence assay (IFA). Serological results were interpreted according to the 2017 guidelines for the detection of Rickettsia spp. Three seroreactive patients had detectable IgM antibodies to Rickettsia with an endpoint titre of 32 and IgG antibodies with endpoint titres of 128 and 256. These findings supported a diagnosis of Rickettsia exposure amongst these patients and highlight that rickettsioses may be among the cause of unknown febrile syndromes in Angola. Therefore, physicians must be aware of this reality and must include this vector-borne disease as part of aetiologies that should be considered and systematically tested in order to delineate appropriate strategies of diagnostic and control of Rickettsia in Angola.